Caracterização do gene ftsH de Streptomyces sp Y7 - Paixão, Cinthia Ferreira da (2002)
The actinomycets are Gram-positive bacterias, aerobic with rich DNA in G+C (larger than 60%) and immobile. They are found practically in all the environment, forming ramified filaments or hyphae that persist in the mycelium form. The Streptomyces constitutes 90% of the isolated actinomycets of the soils, in spite of they are also found in aquatic atmospheres and interior of some plants. They stand out for the diversity of production of hidrolytics enzymes and antibiotics, 70% of the know antibiotics are produced by those microorganisms. Aiming to clone genes with biotechnological interest, a genomic libraries of the Streptomyces sp Y7 isolated of the soil of Cerrado was constructed. After the analyses of the sequences of the genomics libraries of Streptomyces sp Y7, it was selected a plasmid named pFS8, that displayed similarity with ftsH genes. The ftsH gene encodes a metalloprotease ATPase and Zn+2 dependent, belongs to the AAA family (ATPases associated with a variety of cellular activities). It is involved with several cellular functions such as secretory proteins export and degradation of transcriptional factors (sigma 32 and Lambda CII). The data of sequencing showed that the ftsH gene was incomplete. In order to characterize if the product of this gene showed biological activity, it was made tests to evaluate the functionality of the fusions proteins in an ftsH-negative E.coli strain AR3291. AR3291 cells transformed with this plasmid showed a general growth advantage upon the cells AR3291. The protein produced did not present toxicant effects for cells AR3289, which had normal ftsH gene. The truncated protein obtained was also analyzed to prediction of the structure “coiled-coil”, that is common to the other FtsH studied, and the results showed those truncated proteins did nor form “coiled-coil” structure. We also tested whether fusion proteins decreased or inhibited the defective transfer of citosolic proteins.